Dual-Energy Computed Tomography as an Alternative Noninvasive Study for Evaluation of Chronic Thromboembolic Pulmonary Hypertension Postoperatively. (May 2020) - Desai, Anand; Malaisrie, S. Chris; Cuttica, Michael; Freed, Benjamin H.; Rich, Stuart; Schimmel, Daniel; Avery, Ryan
Abstract : Supplemental Digital Content is available in the text.